2021
DOI: 10.3991/ijim.v15i17.22411
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the Actions of a Continuous Distance Training Session for Teachers and its Impact on Their Actual Practices

Abstract: <p><strong><span style="vertical-align: inherit;"><span style="vertical-align: inherit;">Abstrait-</span></span></strong></p><p class="0abstractCxSpFirst"><span lang="EN-US"><span style="vertical-align: inherit;"><span style="vertical-align: inherit;">Ce travail vise à étudier comment une expérience de formation à distance de trois jours pour enseignants, programmée d'urgence, pour développer chez ces enseignants les capacités d'utilisatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…One path we have already partly followed is the introduction of a higher degree of distance-learning or mobile-learning elements in the course. The graduates of qualifying studies should be prepared to use these forms of learning as well, according to research conducted among school principals [31,32]. This will require an improvement in the technological equipment of the university and at the same time an increase in the competence of the course lecturers.…”
Section: Perspective Of the Course Development In The Context Of The ...mentioning
confidence: 99%
“…One path we have already partly followed is the introduction of a higher degree of distance-learning or mobile-learning elements in the course. The graduates of qualifying studies should be prepared to use these forms of learning as well, according to research conducted among school principals [31,32]. This will require an improvement in the technological equipment of the university and at the same time an increase in the competence of the course lecturers.…”
Section: Perspective Of the Course Development In The Context Of The ...mentioning
confidence: 99%
“…However, the effort made to train teachers doesn't meet the exigencies for quality education (CSEFRS, 2014). Tamani et al (2021) stated that the results of their study "reveal the dissatisfaction of these trainee teachers with the qualifying training they have carried out "The USAID study in 2014 showed that most teachers (87%) of teachers who are in training and (70%) of teachers practicing in educational institutions are not satisfied with their training that is very theoretical and does not meet the requirements of their profession. Based on this research, here are some practical recommendations for improving the quality of teachers' training.…”
Section: Relationships Between Mathematics Grades Procedural and Conc...mentioning
confidence: 99%